Analisis Gambaran Histopatologi Gastritis Kronik dengan dan Tanpa Bakteri Helicobacter pylori Menurut Sistem Sydney - Deassy Ariefiany; Abdul Hadi Hassan; Birgitta M Dewayani; Anglita Yantisetiasti (Majalah Patologi Indonesia, 2016)
Background Histopathology definition of chronic gastritis is a chronic inflammation of the gastric mucosa that can cause glandular atrophy and intestinal metaplasia of the gastric mucosal epithelium. Chronic gastritis can be caused by many factors. The most common etiology chronic gastritis by the bacterium Helicobacter pylori (Hp). The incidence chronic gastritis causes of Hp is more common in developing country than developed country. Histopathological picture on chronic gastritis causes of Hp similar with chronic gastritis non-Hp. The aims of this study to determine the difference of histopathological picture between chronic gastritis with Hp and chronic gastritis without Hp bacteria in the Hospital Dr Hasan Sadikin Bandung. Methods The sample used in this study were 30 cases of chronic gastritis with Helicobacter pylori (Hp) and 30 cases of chronic gastritis non-Hp bacteria from the Pathology Department of the hospital Dr. Hasan Sadikin Bandung. The research start from May 1st until November 30th 2012. All sample cases histopathology is seen the image of the Sydney sistem classification, after that are staining with immunohistochemical with antibody monoclonal Hp was performed to confirm the presence of the Hp. Results Immunohistochemical staining result obtained from 42 cases of the bacteria Hp positive and 18 negative cases the bacteria Hp. Chronic inflammation in chronic gastritis with Hp with chronic gastritis without Hp bacteria are in category 3 (limfosit cell more than 20/10HPF) as much as 88,1% and 88,9%. Conclusion Histopathological picture of chronic gastritis with Hp bacteria did not differ with chronic gastritis without Hp bacteria. Key words: Chronic gastritis, Helicobacter pylori, Sydney system.